Konsep Perlindungan Nasab dalam Perspektif Hukum Islam - Restu Ashari Putra; Reza Pahlevi Dalimunthe; Rizal Abdul Gani (Mutawasith: Jurnal Hukum Islam, 2021)
Benefit as the core of maqâshid al-syariah has an important role in the development of Islamic law. Because Islamic law was revealed with the aim of presenting the benefit of humans, both in this world and in the hereafter. One of the benefits that are protected is the protection of lineage. Nasab is human nature, because humans have the instinct to regenerate. On the other hand, humans have the nature of obedience to God. So that the two natures accumulate in lineage protection. Lineage protection is concerned with quantity on the one hand, and quality on the other. The exact point proportions of the two are seen from the bounded realm of reality. Lineage protection is not only about regeneration, but also includes all intermediaries (wasilah) that support it, both in terms of quantity and quality. The purpose of this study is to find out what things can damage the lineage, such as adultery, incest marriage, prostitution and so on.